2009
DOI: 10.1021/bm801296r
|View full text |Cite
|
Sign up to set email alerts
|

Wet-Spinning of Recombinant Silk-Elastin-Like Protein Polymer Fibers with High Tensile Strength and High Deformability

Abstract: A recombinant silk-elastin-like protein copolymer SELP-47K containing tandemly repeated amino acid sequence blocks from silk, GAGAGS, and elastin, GVGVP, was fabricated into microdiameter fibers using a wet-spinning technique. Raman spectral analysis revealed the formation of antiparallel beta-sheet crystals of the silk-like blocks. Dry SELP-47K fibers display the dependence of mechanical properties such as Young's modulus on fiber diameter, suggesting more oriented and crystallized molecular chains in small-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 36 publications
2
96
0
Order By: Relevance
“…The highly dynamic behavior of the flexible RLP chains is reported to be derived from hydrogen bond exchange, charge interactions, and the high polarity of the side chains; the elastomeric properties of the RLP-based materials here is consistent with this behavior. (Kappiyoor et al, 2011) The applied shear stresses (50–4000 Pa) in our experiments, selected for deformation of the RLP-based hydrogels to physiologically relevant strains, are significantly lower than those applied (30 KPa–0.8 MPa) in the characterization of elastin-like polypeptide- (ELP) and silk-elastin like polypeptide(SELP)-based biomaterials (McPherson et al, 1992; Wu et al, 2008; Qiu et al, 2009, 2010; Teng et al, 2009), owing to the fact that the RLP-based hydrogels are more soft and extensible than the previously reported materials.…”
Section: Resultsmentioning
confidence: 90%
“…The highly dynamic behavior of the flexible RLP chains is reported to be derived from hydrogen bond exchange, charge interactions, and the high polarity of the side chains; the elastomeric properties of the RLP-based materials here is consistent with this behavior. (Kappiyoor et al, 2011) The applied shear stresses (50–4000 Pa) in our experiments, selected for deformation of the RLP-based hydrogels to physiologically relevant strains, are significantly lower than those applied (30 KPa–0.8 MPa) in the characterization of elastin-like polypeptide- (ELP) and silk-elastin like polypeptide(SELP)-based biomaterials (McPherson et al, 1992; Wu et al, 2008; Qiu et al, 2009, 2010; Teng et al, 2009), owing to the fact that the RLP-based hydrogels are more soft and extensible than the previously reported materials.…”
Section: Resultsmentioning
confidence: 90%
“…Fourier transform infrared spectroscopy spectra [68] and circular dichroism spectra [25, 68] confirmed that insoluble tightly packed beta sheet structures were formed in silk-like blocks in SELPs. The silk units in SELPs impart the mechanical stability by forming beta sheet physical crosslinks [49, 64] and facilitate the self-assembly of SELPs into micellar-like nanoparticles by phase separation [25]. The elastin-like block (GXGVP) in SELPs is adopted from mammalian tropoelastin [98, 99].…”
Section: Sequence-structure-function Relationships Of Silk-elastinmentioning
confidence: 99%
“…The infrared signatures of the proteins were monitored throughout the chemical modification process (Figure 3B). A broad N-H wagging absorption at 700–900 cm −1 attributed to the primary amine groups of lysine residues on tropoelastin disappeared after the acetylation reaction, as accompanied by the appearance of a C–N stretching vibration peak at 1034 cm −1 attributed to secondary amine groups [20,21]. After enzymatic couplings between S and E′, an increase in the phenolic C–O stretching band was observed at 1290 cm −1 and a decrease in the di-substituted aromatic ring C–C stretching band associated with tyrosine at 1512 cm −1 , both suggesting the formation of dityrosine bonds [22,23].…”
Section: Resultsmentioning
confidence: 99%